2020
DOI: 10.3390/plants9060710
|View full text |Cite|
|
Sign up to set email alerts
|

Together for the Better: Improvement of a Model Based Strategy for Grapevine Downy Mildew Control by Addition of Potassium Phosphonates

Abstract: Grapevine downy mildew is one of the major diseases in viticulture. To control this disease, a more effective strategy has been developed and established based on growth and model data as well as on a combination of fungicides. For this purpose, the systemic plant protection product potassium phosphonate (PP) was combined with two contact fungicides. Treatments were carried out according to the different experimental conditions after the growth of 400 cm2, 600 cm2, and 800 cm2 leaf area per primary shoot. PP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Assuming favourable conditions for P. viticola in 2022, comparable data under standardized conditions could be available by the end of the year, opening the way for a promising new copper fungicide. Since currently available copper fungicides perform particularly weak on grapes this may be an important perspective for organic winegrowers (Bleyer et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming favourable conditions for P. viticola in 2022, comparable data under standardized conditions could be available by the end of the year, opening the way for a promising new copper fungicide. Since currently available copper fungicides perform particularly weak on grapes this may be an important perspective for organic winegrowers (Bleyer et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…German eco-associations have furthermore committed themselves to 17.5 kg within five years (3 kg/ha/year with option to increase up to 4 kg/ha/year at high infection pressure). Years with particularly high P. viticola infection pressure like 2016 and 2021 in Germany therefore lead to existential problems in the organic wine-growing industry, especially since potassium phosphonate is banned in organic winegrowing since 2013 (Bleyer et al, 2020). Moreover, negative effects of copper on the environment like a reduction in biodiversity of soil micro-and macroorganisms (Merrington et al, 2002;Buenemann et al, 2006) were reported.…”
Section: Introductionmentioning
confidence: 99%
“…& De Toni, can lead to epidemic infestation in years with suitable warm and humid weather conditions and thus high crop losses (Figueiredo et al, 2017;Unger et al, 2007). In years of high infestation pressure, such as 2012, 2016, and 2021, limited copper levels pose enormous challenges for organic growers to adequately protect their vineyards from downy mildew (Bleyer et al, 2020). A reduction of the copper application amount in such years is not possible at all.…”
Section: Introductionmentioning
confidence: 99%
“…The required weather information is collected via weather stations which have been set up in large numbers throughout the winegrowing regions. Taking into account this data and additional phenology models for vine development, recommendations are made to the winegrowers in order to make plant protection as effective and sustainable as possible (Bleyer et al, 2008;Bleyer et al, 2020;Dubuis et al, 2019;Rossi et al, 2014). The forecasting system VitiMeteo, which has been developed by Agroscope (Changins, Switzerland) and the State Institute for Viticulture (Freiburg, Germany) refers to the calculations of the area of newly grown leaves per primary shoot for the recommendations of the treatment intervals (Bleyer at al., 2020;Bleyer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation